Teaching of pharmacology in Universiti Malaya and the other medical schools in Malaysia - a historical perspective - Sim, S.M. (2004)
Traditional pharmacology teaching has focused more on drug instead of therapeutics, such that although pharmacological knowledge is acquired, practical skills in prescribing remain weak. In Malaysia many new medical schools (both public and private) have been set up in the last 12 years due to a change in government policy, resulting in a wide spectrum of medical curricula. Universiti Malaya (UM) being the oldest medical school in Malaysia was deep set in its traditional way of teaching-learning, since its inception in 1962, until a visit from the General Medical Council of the United Kingdom in 1984 triggered off a change of tide. Since then the medical curriculum in UM has undergone two major revisions. The first revised curriculum (1988) aimed to inject more clinical relevance into basic science teaching, through introducing clinical lectures and skills in the paraclinical year. Professional behaviour was also addressed. The second revised curriculum (1998) sought to improve further the integration of knowledge as well as to produce a holistic doctor, viewing the patient as a person instead of a clinical entity. The teaching-learning of pharmacology has gradually moved from factual regurgitation to more clinical reasoning, from lab-based to more patient-oriented approach. As more new medical schools are being set up in Malaysia, exchange of experience in this area of learning will hopefully help us find a happy medium between "the old is best" and "the new is better" type approach so that a pedagogically sound and yet logistically practical curriculum can be found in our local setting, to help produce doctors with good prescribing practice.